Presuposisi Dalam Strategi Branding Kosmetik Di Shopee Live - Ziyan Annisah; Nasiha Amirotul Khoiriyah; Tatu Siti Rohbiah (Universitas Swadaya Gunung Jati, 2026)
This study aims to comprehensively analyze the pragmatics ofpresuppositions used in cosmetics branding on Shopee Live and toidentify the linguistic strategies used by sellers in buildingrelationships with buyers. This study adopted a descriptivequalitative method, using observational data from ten Shopee Livesession recordings of popular cosmetic brands (Emina, Glad2Glow,IMPLORA, Instaperfect, Mother of Pearls (MOP), OMG, Pinkflash,Sea Makeup, Somethinc, and Wardah) recorded between April 19-21, 2025. Data collection involved systematic observation, verbatimtranscription of sellers' conversations, and detailed analysis of theuse of presuppositions and other interpersonal linguistic strategies.The results show that presuppositions serve as a crucial strategiccommunication tool, effective in forming shared assumptions,implicitly conveying product information and benefits, and subtlycreating purchase urgency without explicit commands. Furthermore,this study identified that sellers strategically use presuppositionswithin broader linguistic strategies, such as personal greetings andpersonal usage testimonials, to build closeness and trust, therebyinfluencing buyers' purchasing decisions by appealing to emotionalvalues and fostering brand loyalty